THE EFFECTIVENESS OF PHYSICAL STIMULATION SELF-IMPROVEMENT STUDENTS IN HIGH SCHOOL - Urazov, D.B.; Seitganov, T.B.; Ibraeva, R.G. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
In the article the issues of incentives that motivate a prospective teacher in physical self-improvement is considered. In the research work the incentives to physical self-improvement of a student is categorized and the rating of their impor-tance is made,theoretical barriers to the motivation in physical self-improvement of a student are experimentally revealed and substantiated, system-building incenti-ves and their impact on motivation in physical self-improvement of a student are revealed. The most significant incentives in physical self-improvement of a prospective teacher, which include incentives of self-cognition: the sense of per-sonal importance of the problem of physical self-improvement, the sense of the purpose of physical self-improvement, are revealed. Incentives of motivationof self-determination in physical self-improvement are detected. Besides the barriers arerevealed and the rating of constraining importance in stimulating a student in physical self improvement are determined. The results can be used in pedagogical activity by teachers of physical education of higher schools and coaches of sports schools with the purpose of creating the conditions of overcoming the barriers of physical self-improvement and the maximum use of the incentives promoting an increase of efficiency of physical self improvement of a prospective teacher.
Keywords: physical improvement; physical culture; physical exercises; sports activity; healthy lifestyle